Gambaran Pengetahuan Keluarga tentang Perawatan Pasien Stroke - Fatmawati, Ariani (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2020)
Stroke patients treatment started during treatment at the hospital until after being treated. Family knowledge in treating stroke patients at home needs to be improved. The purpose of this study is to find out the description of family knowledge about the care of stroke patients at Al-Islam Hospital Bandung. This research used quantitative descriptive, involving 60 respondents of patients aged over 18 years, living with the patient and engaging in care of patient. The sample use purposive sampling technique. The study was conducted at Al-Islam Hospital Bandung on 1-24 January 2019. The instrument used was a modification of the assessment of the caregiver knowledge and Barthel Index. The analysis used frequency distribution. The results showed that the level of family knowledge in stroke patients in the category was sufficient as much as 31.5% and less as much as 68.5%. Researchers suggest optimizing the existing discharge planning program by conducting studies of the needs of patients and families as well as an intensive education process not only for patients but for their families.